Chemical characteristics and biological activity screening of Pistacia lentiscus mastic gum and leaves from Türkiye - Sarikahya, Nazli Boke; Okkali, Gaye Sumer; Coven, Furkan Ozan; Isen, Fulya; Goren, Ahmet C.; Nalbantsoy, Ayse (Wiley, 2024)
BACKGROUND: Mastic gum is a resin that is produced by Pistacia lentiscus. It has many traditional uses, dating from ancient times, such as the treatment of gastrointestinal disorders and as a food additive. In this study, the leaves and mastic gum of trees of different ages from Karaburun and the Cesme peninsula in Turkiye were examined chemically and biologically. Flavonoids, and phenolic and fatty acid components were evaluated by a liquid chromatography system coupled with high resolution mass spectrometry (LC-HRMS) and gas chromatography with flame ionization detection (GC-FID). Cytotoxicity was screened against several cancer and healthy cell lines using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Inducible nitric oxide synthase (iNOS) inhibition was determined on lipopolysaccharide (LPS)-induced murine macrophage cell line (RAW 264.7) cells. Antiviral activity was measured against avian coronavirus using an in ovo virucidal antiviral activity assay.RESULTS: The main phenolic constituents of the gum were found to be salicylic, rosmarinic, and caffeic acids whereas the most abundant compounds detected were flavonoids in the leaf extracts. The most abundant fatty acids in hexane extracts were palmitic and oleic acids. All gum extracts except 3-year-old gum had significant cytotoxic activity on HeLa (IC50 1.74 +/- 0.03-4.76 +/- 0.95) and PC-3 (0.64 +/- 0.25-6.22 +/- 1.40) cells. Moreover, reducing virus activity by fivefold or sixfold logarithmically between the range of 5-10 mu g g(-1) of 30-year-old gum extracts underscored the biological activity.CONCLUSION: In ovo antiviral activity studies on the P. lentiscus were conducted for the first time. The mastic gum and leaves obtained from P. lentiscus may have strong potential in terms of their chemical content and antiviral and cytotoxic activity. As a consequence of these properties, it is a sustainable, renewable natural resource that can be used as an additive and flavoring in the food and pharmaceutical industries.(c) 2023 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: Pistacia lentiscus; mastic gum; cytotoxicity; antiviral activity; avian coronavirus